Gambaran Tingkat Kecemasan Mahasiswa Tingkat 1 Fakultas Kedokteran Unisba pada Sistem Pembelajaran Daring Selama Pandemi Covid-19 - Nurmalia Putri; Yuniarti; R. Ganang Ibnusantosa (Bandung Conference Series: Medical Science, 2022)
Abstract. The COVID-19 pandemic was declared a "public health emergency of international concern" by WHO on January 30, 2020, and designated a pandemic on March 11, 2020. The COVID-19 pandemic causes psychological and social effects. One of the psychological effects of the COVID-19 pandemic is anxiety. This anxiety can occur among students. Data from Chang et al in China shows that students have an incidence of mental disorders due to the COVID-19 pandemic, namely anxiety around 26.60%. This study aims to describe the level of anxiety in level 1 students of the Faculty of Medicine, Islamic University of Bandung for the 2020/2021 academic year in the online learning system during the COVID-19 pandemic. The research design used was descriptive observational, with a cross-sectional design. The sample size is 133 first-year students of the Faculty of Medicine, Islamic University of Bandung for the academic year 2020/2021 with a simple random sampling technique, the instrument used is the Zung Self Rating-Anxiety Scale (ZSAS) questionnaire. The results showed that most of the respondents did not experience anxiety as many as 104 people (76%) and the rest experienced mild anxiety as many as 32 people (24%). Students don’t experience anxiety (normal) because of their adaptability to prevent the emergence of anxiety that arises such as interesting learning, doing self-care, namely sleeping, physical activity, and meeting nutritional needs. Students who experience a mild level of anxiety means that students still have to self-focus on things that cause anxiety but are still able to do other activities. Abstrak. Pandemi COVID-19 dinyatakan sebagai "darurat kesehatan masyarakat yang menjadi perhatian internasional" oleh WHO pada tanggal 30 Januari 2020, dan ditetapkan sebagai pandemi pada tanggal 11 Maret 2020. Pandemi COVID-19 menyebabkan efek psikologis dan sosial. Salah satu efek psikologis pandemi COVID-19 yaitu kecemasan. Kecemasan ini dapat terjadi di kalangan mahasiswa. Data dari Chang dkk di negara China menunjukkan bahwa mahasiswa memiliki kejadian gangguan mental akibat pandemi COVID-19 yaitu kecemasan sekitar 26,60%. Penelitian ini bertujuan untuk mengetahui gambaran tingkat kecemasan pada mahasiswa tingkat 1 Fakultas Kedokteran Universitas Islam Bandung tahun ajaran 2020/2021 pada sistem pembelajaran daring selama pandemi COVID-19. Desain penelitian yang digunakan adalah observational deskriptif, dengan rancangan cross sectional. Besar sampel berjumlah 133 mahasiswa tingkat satu Fakultas Kedokteran Universitas Islam Bandung tahun ajaran 2020/2021 dengan teknik simple random sampling, instrumen yang digunakan adalah kuesioner Zung Self Rating-Anxiety Scale (ZSAS). Hasil penelitian menunjukkan sebagian besar responden tidak mengalami kecemasan sebanyak 104 orang (76%) dan sisanya mengalami kecemasan ringan sebanyak 32 orang (24%). Mahasiswa tidak mengalami kecemasan (normal) karena kemampuan adaptasinya untuk mencegah timbulnya rasa cemas yang muncul seperti pembelajaran yang menarik, melakukan perawatan diri yaitu tidur, aktivitas fisik dan memenuhi kebutuhan nutrisi. Mahasiswa yang mengalami tingkat kecemasan ringan artinya mahasiswa masih mempunyai fokus diri terhadap hal- hal yang menimbulkan kecemasan tetapi masih mampu melakukan aktivitas lain.